Applied and Theoretical Research on the Parameter-Dependent Efficiency of a Coilgun - Asriyan, Alexander (European Scientific Journal, ESJ, 2019)
This research paper focuses on determining the dependence of a coilgun’s efficiency on its working parameters. Due to its working principal, the linear acceleration process of a ferromagnetic projectile can be described as a “shot”. The ratio of the projectile’s kinetic energy to the potential energy stored in the capacitors was used to calculate the efficiency of each shot. The equation of force pushing the projectile was derived theoretically. For health and safety reasons, measurements were taken with projectile speeds under 15m/s. A kinematic method was used to measure the speeds of the projectiles. Iron was chosen as the projectile material due to its ferromagnetic properties. After understanding the major factors that affect the coilgun’s efficiency and by optimizing them, an efficiency value of 6.7% was achieved.